Forced sterilization of women living the HIV/AIDS in Africa - Tung, Odile Lim (University of Pretoria, 2010)
A dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Odile Lim Tung, Faculty of Law and Management, University of Mauritius, Mauritius.